Prenatal airborne polycyclic aromatic hydrocarbon exposure, LINE1 methylation and child development in a Chinese cohort. (February 2017) - Lee, Joan; Kalia, Vrinda; Perera, Frederica; Herbstman, Julie; Li, Tingyu; Nie, Jisheng; Qu, L.R.; Yu, Jie; Tang, Deliang
Abstract: Background: Polycyclic aromatic hydrocarbons (PAH) are carcinogenic, neurotoxic environmental pollutants generated during incomplete combustion of fossil fuel and other organic material. PAH exposure has been associated with adverse fetal development and epigenetic alterations in cord blood. Several molecular epidemiology studies have established PAH-DNA adducts as biomarkers of PAH exposure. Objectives: We investigated the relationship between LINE1 DNA methylation and PAH-DNA adduct levels in cord blood, and with neurodevelopmental outcomes. Methods: In Tongliang County, China, the current study enrolled two population-based cohorts of nonsmoking pregnant women before (2002) and after (2005) the closure of a local coal-fired power plant in May 2004. We analyzed cord blood samples collected from mothers in the two cohorts (n = 110 from 2002 cohort and n = 107 from 2005 cohort) for PAH-DNA adducts and genomic LINE1 DNA methylation. Neurodevelopmental data on children were collected using the Gesell Developmental Scales (GDS) at age 2 and using the Wechsler Intelligence Scale for Children (WISC) at age 5. Results: A significant inverse relationship was observed between PAH-DNA adducts and LINE1 DNA methylation (β = − 0.010, p < 0.038). A significant, positive association between LINE1 methylation and scores on WISC full scale and verbal (β = 85.31, p < 0.005; β = 94.36, p < 0.003) but not on the GDS. Mediation analysis did not find LINE1 to be a direct mediator between PAH-DNA adducts and IQ score. Conclusion: LINE1 methylation in cord blood DNA was a positive predictor of IQ at age 5 and was decreased at higher levels of prenatal PAH exposure measured by PAH-DNA adducts in cord blood. However, the adverse effects of prenatal exposure to PAH on IQ scores did not appear to be directly mediated by altered LINE1 methylation. Highlights: PAH-DNA adducts are an integrated index of biologically effective dose of PAH exposure. LINE1 methylation was inversely associated with PAH-DNA adduct level. LINE1 methylation could predict IQ scores at age 5.